2021
DOI: 10.1525/elementa.2020.00174
|View full text |Cite
|
Sign up to set email alerts
|

Applying a novel systems approach to address systemic environmental injustices

Abstract: The knowledge of unsustainable human and Earth system interactions is widespread, especially in light of systemic environmental injustices. Systems science has enabled complex and rigorous understandings of human and Earth system dynamics, particularly relating to pollution of Earth’s land, water, air, and organisms. Given that many of these systems are not functioning sustainably or optimally, how might this field enable both rigorous understanding of the issues and experiments aimed at alternative outcomes? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 203 publications
(236 reference statements)
0
5
0
Order By: Relevance
“…The fundamental issue is to prevent Pb exposure by children in the first place. Egendorf, Groffman, et al (2021) described the systemic interactions of humans and soil Pb at various scales in time and space. They discussed interventions for mitigating soil Pb exposure at each scale and provided examples of applied and participatory experiments to mitigate exposure at different scales currently being conducted in New York City, NY, USA.…”
Section: Remobilized Urban Lead Dust From Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…The fundamental issue is to prevent Pb exposure by children in the first place. Egendorf, Groffman, et al (2021) described the systemic interactions of humans and soil Pb at various scales in time and space. They discussed interventions for mitigating soil Pb exposure at each scale and provided examples of applied and participatory experiments to mitigate exposure at different scales currently being conducted in New York City, NY, USA.…”
Section: Remobilized Urban Lead Dust From Soilmentioning
confidence: 99%
“…They discussed interventions for mitigating soil Pb exposure at each scale and provided examples of applied and participatory experiments to mitigate exposure at different scales currently being conducted in New York City, NY, USA. (Egendorf, Groffman, et al., 2021 )” The intervention of Pb‐contaminated soils has received attention from researchers in nations around the world (Laidlaw et al., 2017 ). Mapping soil Pb is an important first step, for example, Figure 1 (Mielke et al., 2022 ).…”
Section: Applying a Systems Approach To Address Systemic Injustices A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lead adhering to soil particles may move down a soil profile over decadal scales, or Pb concentrations may be diluted as organic matter and other amendments are added to surface layers (Mielke et al., 2019). However, the legacy of Pb in urban soils continues to pose risks to urban populations, especially young children (Egendorf, Groffman, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…After an initial test, Mun began to work with Brooklyn College's Soil and Microbiology Lab to research whether the fungi could break down long-chained toxins found in the creek's groundwater. However, like Chin's work, Mun's efforts could not extract a significant concentration of contaminants from the site(Egendorf et al 2021). The project was successful in other ways, though, bringing together diverse communities across the city to participate in hands-on workshops and training, producing educational materials, and highlighting the potential for bioremediation strategies to remediate the creek.…”
mentioning
confidence: 98%